A cross-sectional study on prevalence of gastro esophageal reflux disease in regurgitant infant and children with evaluation of IGERQ score - Kandasamy, Elayaraja; Andy, Senthil Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: Gastro Esophageal Reflux Disease (GERD) is the most common esophageal disorder in children of all ages. GER becomes pathological when reflux increase in frequency and intensity, associated with esophageal and respiratory symptoms. Thus, the study was determined to assess the prevalence of GERD in regurgitant children of age 6 to 24 months with evaluation of IGERQ score (Infant Gastro Esophageal Reflux Questionnaire). Methods: A descriptive study was conducted in Gastroenterology Department, Institute of child Health and Hospital for Children, Egmore, Chennai from September 2007 to September 2009. 123 regurgitant children of age 6-24 months were enrolled. Clinical examination and validated questionnaire with total score of 25 was used. Data analysis was aided by EPI info programme. Chi square with P value <0.05 was considered statistically significant. IGERQ score was evaluated by calculating sensitivity, specificity, positive predictive valve and negative predictive valve. Results: The prevalence of GERD in regurgitant infant and children is 30.8%. Refusal of feeds and poor weight in regurgitant children significantly correlated with GERD. sensitivity was 84%, specificity was 96%, positive predictive value was 91%, negative predictive value was 93% Conclusions: Clinical diagnosis of GERD is sufficient in most instances and a questionnaire may aid in diagnosis the disease. IGERQ score is easily adaptable. IGERQ score >5 has high specificity positive and negative predictive value but reproducibility in our population need further evaluation.